Integration of foot massage and diabetic foot gymnastic on peripheral perfusion in patients with diabetes mellitus 2 - Clara Puryanti; Paulus Subiyanto; Thomas Aquino Erjinyuare Amigo (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2023)
The prevalence of Type 2 Diabetes Mellitus (DMT2) is increasing yearly. Peripheral neuropathy of the foot is a complication that often appears in people with diabetes. Neuropathy disorders that are not treated properly can risk causing diabetic ulcers and even amputations. Complementary therapies that can be done to overcome this are foot massage and diabetic foot exercises.Â  This study aims to determine the effect of integrating foot massage and diabetic foot gymnastics to overcome complaints of peripheral tissue perfusion in the feet of DMT2 patients at the Polyclinic of Panti Nugroho Hospital. Quasi-experimental research method with Pretest-Posttest Control Group Design design. The intervention and control groups each consisted of 15 respondents.Â  The intervention group was given foot massage treatment and diabetic foot exercises for three consecutive days for 15 minutes. The independent t-test and Mann-Whitney test were used to analyze the data. There were significant differences in ABI scores, oxygen saturation, and monofilament scores in the intervention group's left and right legs against the control group (p-value < 0.05). There is a significant effect of the integration of foot massage and diabetic foot gymnastics on peripheral tissue perfusion in both the left leg and right foot of T2DM patients. The contribution of this study needs further research with a larger number of respondents and a longer time to ascertain its effectiveness before it is used as part of local nursing intervention standards.